Metamaterials and Metasurfaces - Ojaroudi Parchin, Naser; Ojaroudi, Mohammad; Abd-Alhameed, Raed A (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Metamaterials and metasurfaces have recently attracted increasing attention due to their anomalous and largely flexible properties. Their performance mainly depends on their subwavelength separation and geometric parameters. Metamaterials comprise a class of artificial materials whose physical properties can be engineered to exhibit various desired characteristics. A metasurface is a 2D metamaterial whose thickness is well below the wavelength of impinging lights. Metamaterials and metasurfaces have unique interface transmission and reflection properties resulting from surface impedance, which can cause multiple advanced functionalities such as light focusing, hologram generation, polarization control, etc. Their extremely small hardware footprint enables them to be embedded in various components of the environment in a cost-effective way. In recent years, they have emerged as a powerful technology with a broad range of applications; however, there are many challenges yet to be addressed in order for them to fulfil their potential in practical applications.This Special Issue reprint covers all aspects of metamaterials and metasurfaces. It also aims to highlight the exciting developments, ongoing trends, and latest achievements in their design and construction.